2000
DOI: 10.1086/315469
|View full text |Cite
|
Sign up to set email alerts
|

Disease Progression and Survival with Human Immunodeficiency Virus Type 1 Subtype E Infection among Female Sex Workers in Thailand

Abstract: This study describes rates and correlates of disease progression and survival among 194 female sex workers in northern Thailand who were infected with human immunodeficiency virus type 1 (HIV-1; 96% with subtype E). The median rate of CD4 T lymphocyte decline (3.9 cells/microL/month), median time from infection to <200 CD4 T lymphocytes/microL (6.9 years), and time to 25% mortality (6.0 years) were similar to those found in studies performed in Western countries before highly active antiretroviral therapy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 41 publications
(69 reference statements)
4
27
3
Order By: Relevance
“…Thus, our findings are generally in agreement with those of the previous studies from both developed and developing world populations, although our survival rates are on the low end of these ranges. Studies among HIV-1-infected female commercial sex workers have suggested more-rapid disease progression [7,33,38], potentially as a result of low socioeconomic status, sexually transmitted diseases, and greater viral genetic diversity [32,39]. Nevertheless, our results do not suggest that the natural history of HIV-1 infection among adults in Africa differs substantially from that observed in the industrialized world in the absence of antiretroviral treatment.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Thus, our findings are generally in agreement with those of the previous studies from both developed and developing world populations, although our survival rates are on the low end of these ranges. Studies among HIV-1-infected female commercial sex workers have suggested more-rapid disease progression [7,33,38], potentially as a result of low socioeconomic status, sexually transmitted diseases, and greater viral genetic diversity [32,39]. Nevertheless, our results do not suggest that the natural history of HIV-1 infection among adults in Africa differs substantially from that observed in the industrialized world in the absence of antiretroviral treatment.…”
Section: Discussioncontrasting
confidence: 71%
“…The largest study of mortality among a seroprevalent HIV-1 cohort from Africa included 197 individuals from rural Malawi and found a median survival duration of 8 years [6]. Studies from other developing countries suggest similar survival; for example, among 194 female sex workers in Thailand, 25% mortality occurred at 6.0 years [33]. Data from industrialized nations from before the introduction of HAART demonstrated 25% mortality at 6-10 years after HIV-1 acquisition [34,35] and median survival duration of 8-13 years [8,36,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the estimated loss in absolute CD4 numbers in placebo group agrees well with published longitudinal surveys in a comparable group of patients who either did not respond to HAART or interrupted their treatment (Palella et al, 2003;Tebas et al, 2002). This estimate is also in agreement with a longitudinal survey of disease progression among non-treated female sex workers in northern Thailand, with median decline of −3.9 CD4 cells/month (Kilmarx et al, 2000). A similar rate of progressive lymphocytopenia equivalent to −3.2 cells/month has been reported among 605 injecting drug users who started with a median 513 CD4 lymphocytes (Lyles et al, 1997).…”
Section: Discussionsupporting
confidence: 88%
“…The slope was then used to divide the cohort into two groups as faster progressors and slower progressors. We arbitrarily used a CD4 þ count slope of À75 cells/ml/year to separate faster progressors and slower progressors, which is comparable to a median CD4 þ slope in a Thai HIV natural history cohort [Kilmarx et al, 2000]. The slopes of subjects in the two groups are shown in Figure 1.…”
Section: Cd4mentioning
confidence: 99%